PERANCANGAN GANTRY CRANE KAPASITAS 10 TON DENGAN BANTUAN SOFTWARE - Endi Sutanto; G Soeharsono (Program Studi Teknik Mesin Universitas Tarumanagara, 2017)
Abstract: Gantry crane is one of the lifting machines that use to lift and move loads which can’t lift by human power. The Applications of gantry crane can be seen at sea port area and loading area in industrial. The design of gantry crane must be applied to find the strength and endurability for the gantry crane. Design of gantry crane consists of hoisting mechanism and structure design. The design of gantry crane with 10 tons of capacity and 15 meters of span also applying strength analysis using auto desk inventor software will be discussed in this paper.